Biological therapies for the treatment of cutaneous wounds: Phase III and launched therapies. (November 2013) - Rennert, Robert C; Rodrigues, Melanie; Wong, Victor W; Duscher, Dominik; Hu, Michael; Maan, Zeshaan; Sorkin, Michael; Gurtner, Geoffrey C; Longaker, Michael T
<x xml:space="preserve">Abstract</x> Introduction: Normal wound healing mechanisms can be overwhelmed in the setting of complex acute and chronic tissue injury. Biological therapies are designed to augment and/or restore the body's natural wound healing abilities. There are a variety of available and emerging technologies utilizing this approach that have demonstrated the ability to augment wound healing. Areas covered: In this review, the clinical data on launched and emerging biological therapies for wound healing applications are summarized. The methodologies discussed include biological skin equivalents, growth factors/small molecules and stem cell-based therapies. Expert opinion: While many products possess convincing clinical data demonstrating their efficacy in comparison to standard treatment options, more robust, controlled studies are needed to determine the relative value among established and emerging biological therapies. Future bioengineering and stem cell-based approaches are of particular interest due to the simultaneous correction of multiple deficiencies present in the nonhealing wound.